CFD modelling of carbon capture in large-scale for structured packed bed column. - Hossain, Mohammad Ashraf (Cranfield University, 2021)
In this Ph.D. thesis, a novel 3D numerical model is developed to solve multiphase flow problem for carbon capture. The model solves the Navier-Stokes equations with commercial solver Ansys Fluent with higher accuracy and much better prediction. The proposed model was at first developed to solve the hydrodynamics problem inside the structured packed bed. In the hydrodynamic part, viscous resistance and inertia resistance for both gas and liquid were taken into account and were implemented by the User Defined Function (UDF). The structured mesh was done using ICEM-CFD. In this part, dispersion forces were also included by UDF. Hydrodynamics of the structured packed bed was validated in terms of liquid volume fraction and, a higher degree of accuracy was achieved. This achievement was done by implementing drag law in a novel way. Dispersion of the liquid inside the packed bed was modelled both by mechanical dispersion and by spread tensor. Pressure drop is a very important part of designing structured packing and, it has to be kept to a minimum. In the hydrodynamics study, this pressure drop was kept minimum, and a good distribution of gas and liquid was achieved. The second part of the model is the chemical reactions. In this case, all the five reactions that occur in carbon capture were taken into account along with the hydrodynamics. Few studies like the effect of solvent concentration, the effect of pressure were studied by using this part of the model. Another novel aspect of the model is that it can predict gas-liquid interfacial area and enhancement factor for chemical reactions. As a result, it has become much easier to understand chemical reactions and calculate carbon removal easily. The third part of the model is the heat transfer effect. Heat transfer effect was included by changing gas and liquid temperature and it was found that liquid temperature has a wider impact on carbon capture. All the contributions to the knowledge were summarized in Chapter 7.
Keywords: multiphase flow problems; carbon capture; Navier-Stokes equations; Ansys Fluent solver; hydrodynamics; viscous resistance